THE IMPLEMENTATION OF MIND MAPPING TECHNIQUE IN IMPROVING STUDENTS’ MOTIVATION OF WRITING - Lilik Fauziyah (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2022)
This research is motivated by the lack of student motivation in writing report texts. This study aims to increase the writing motivation of class IX D students of SMP Negeri 1 Kabuh by using the Mind Mapping technique. This technique was chosen to increase student motivation so that students are enthusiastic in expressing their ideas in writing. To achieve this goal, the researcher determined the criteria for success, more than 70% of students were motivated during the writing process. This classroom action research uses the Kemmis and Taggart model using 4 steps, namely planning, implementation, observation, and reflection. This research was conducted in two cycles. Data were obtained through observation sheets and questionnaires. The results of the study indicate that the Mind Mapping technique is able to increase students' motivation in writing report texts. This can be proven by increasing student motivation. In the pre-writing, in cycle 1 to cycle 2 it increased from 66% to 84%. For the drafting, in cycle 1 to cycle 2, from 56% increased to 75%. For the revising, in cycle 1 to cycle 2, from 47% increased to 72%. And for the editing, in cycle 1 to cycle 2, from 63% increased to 81%.